2012
DOI: 10.1074/jbc.m112.402784
|View full text |Cite
|
Sign up to set email alerts
|

Rad9 Protein Contributes to Prostate Tumor Progression by Promoting Cell Migration and Anoikis Resistance

Abstract: Background: Rad9, a cell cycle checkpoint and DNA repair protein, is functionally related to human prostate tumorigenesis. Results: Rad9 deletion in prostate cancer cells impairs migration and invasion, sensitizes to anoikis, and down-regulates integrin ␤1. Conclusion: Rad9 controls ITGB1 expression, migration, invasion, and anoikis resistance of prostate cancer cells. Significance: This study reveals the significance of Rad9 in prostate tumor migration and invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…With the advantages of specificity and high efficiency, the siRNA technique has become a common reverse genetics method of gene function research both in vivo and in vitro [29]. Suppression of endogenous Annexin A3 in BGC823 cells using siRNA, inhibited gastric cancer cell proliferation, promoted the expression of cell cycle negative regulators, p21 and p27, and suppressed the expression of cyclin D1, which enhances cell proliferation by promoting cell cycle progression from G1-S [32,34]. We also found that expression of the cellular proliferation marker, PCNA, decreased after Annexin A3-siRNA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advantages of specificity and high efficiency, the siRNA technique has become a common reverse genetics method of gene function research both in vivo and in vitro [29]. Suppression of endogenous Annexin A3 in BGC823 cells using siRNA, inhibited gastric cancer cell proliferation, promoted the expression of cell cycle negative regulators, p21 and p27, and suppressed the expression of cyclin D1, which enhances cell proliferation by promoting cell cycle progression from G1-S [32,34]. We also found that expression of the cellular proliferation marker, PCNA, decreased after Annexin A3-siRNA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancement of invasion/migration abilities provides the basis for tumor metastasis, which is the result of malignant tumor progression [34]. Previous studies have reported that Annexin 1-deficient neutrophils exhibit enhanced transmigration in vivo [35].…”
Section: Discussionmentioning
confidence: 99%
“…Further, RAD9 functions in tumor metastasis, and thus its activity is not limited to initial tumor formation. Down regulation of RAD9 in prostate cancer cells in culture impairs metastasis-related phenotypes, including migration, invasion, and anchorage-independent growth, as well as sensitizes those cells to anoikis (41,42), which is programmed death induced when cells are not attached to a matrix (43). Typically, metastatic cells are anoikis resistant, enabling them to remain viable as they travel through the bloodstream for eventual localization in distal sites.…”
Section: Rad9 and Prostate Cancermentioning
confidence: 99%
“…Typically, metastatic cells are anoikis resistant, enabling them to remain viable as they travel through the bloodstream for eventual localization in distal sites. RAD9 affects cell migration and invasion by modulating integrin β1 protein level, and anoikis resistance by modulating AKT kinase activation (42). …”
Section: Rad9 and Prostate Cancermentioning
confidence: 99%
“…For example, anoikis promotes the luminal clearance during mammary gland development, which to some extent explains the formation of our inner organ (Debnath, 2008). Moreover, a bulk of evidences has proved that anoikis resistance is intimately involved in the tumorigenesis and metastasis of various cancers, such as lung, colon, and prostate cancers (Horbinski et al, 2010;Broustas et al, 2012;Taddei et al, 2012;Vigil et al, 2012;Zheng et al, 2012). Therefore, the studies and summarizations of the regulatory mechanism(s) of anoikis are fundamental to the intervention of tumor metastasis.…”
mentioning
confidence: 99%